Frugal Education: What, why, and how? - Alex Masters (Future in Educational Research)
Abstract This paper explores how frugal innovation practices can challenge resource constraints by leveraging available resources in creative and innovative ways towards more affordable, practical, sustainable and resilient education practice. The education sector has faced many challenges when adapting practice to deliver quality education in the wake of a world‐changing pandemic. There is a great deal we can learn from each other with regards to the frugal application of resources, such as time, money, people and space. However, forms of frugality in education design are driven by necessity and are reactive as opposed to proactive measures. We can, however, learn from educators and institutions that have been able to achieve significant educational impact at low cost with far fewer resources, adopting frugal approaches to education design and delivery. This paper proposes a set of frugal education aspects that demonstrate how frugal design practices can be organised and applied within an educational context. The aspects are outlined, and examples are presented to illustrate their effectiveness within existing education practice. This paper seeks to contribute to the existing knowledge base and research into frugal innovation practice as it applies within an education context, reframing the use of the term ‘frugal’ away from affordability and poor quality, towards a more expansive understanding that establishes a foundation on which to build, define, and contextualise frugality within an education context. The paper concludes with recommendations for the development of practical resources, informed by the research, to support educators in the design of frugal education practice.